Implementation of Guessing The Picture For Increase The English Vocabulary of Students - Ervina Ampulembang; Nasriandi Nasriandi; Syahrir Syahrir; Husnani Aliah (Edumaspul: Jurnal Pendidikan, 2023)
English is the language of communication in the international world, even in the fields of development, technology, economics, and education. Being CPNS (Civil Servant Candidates), work in companies with high salaries, and one of the true forms of getting a scholarship is that many universities require a TOEFL or IELTS as a requirement for graduation. Vocabulary is the most important component that youngsters must master in order to be able to utilize the language effectively. The aim of this article is to present results from research on guessing photographs using paper targeted to students, as well as as an additional tool, namely students must use a dictionary when the picture is shown and the English vocabulary from the picture is unknown to them. An experimental strategy is used in this study procedure. Researchers employ the Quasi Experimental Design technique, in which the first stage is orientation or school observation, followed by the selection of the sample and population to be used as research material. The team gave a favorable response from step one through step three based on the results of the checklist and field notes examined during the study process, indicating that the team had improved. According to the data, playing the photo guessing game enhanced effective vocabulary. The number of participants in the experimental class increased after the post-test phase, whereas the number of participants in the control class did not. The experimental class's post-test scores can be seen in the post-test results to confirm it.